A purification and impurity control method for preparing high purity metallic chromium
Patent Information
- Application Number
- CN202311602611.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-28
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-11-28
AI Technical Summary
现有技术中金属铬的生产方法有铝热法、电解法和电硅热法,得到的金属铬中的杂质含量较高,纯度较低,成品率较低,很难满足航空航天、核电等领域特种装备对金属铬的严苛要求,因此,研究对现有金属铬进行再次提纯制备高纯金属铬的方法具有重要意义
[0019](1)本发明基于电铝热法普通金属铬在低温下易脆化、易粉碎等特点,采用液氮粉碎机进行研磨制粉,制得金属铬粉粒径均匀,再采用球磨进行研磨混料,使得金属铬粉与添加剂混合更加均匀,增加了混合料的接触面积,更利于反应进行,接着采用高剪切混合器混合粉末与粘合剂,利用高剪切作用,能够有效提升混合效率,防止物料团聚。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-purity metallic chromium preparation technology. More specifically, this invention relates to a purification and impurity control method for preparing high-purity metallic chromium. Background Technology
[0002] High-purity metallic chromium, due to its high melting and boiling points, high hardness, high temperature resistance, corrosion resistance, and good toughness, is widely used in metallurgy, electronics, aviation, and aerospace, primarily for the production of high-temperature alloys and sputtering targets. In recent years, with the rapid development of my country's aerospace industry, the demand for high-purity metallic chromium specifically for high-temperature alloys and sputtering targets has been increasing. However, these applications require strict control over the impurity content of high-purity metallic chromium, demanding high purity and low impurity content. Existing methods for producing metallic chromium include the aluminothermic process, electrolysis, and electrosilicon thermal process. These methods result in metallic chromium with high impurity content, low purity, and low yield, making it difficult to meet the stringent requirements of special equipment in aerospace, nuclear power, and other fields. Therefore, researching methods for further purifying existing metallic chromium to prepare high-purity metallic chromium is of great significance. Summary of the Invention
[0003] One object of the present invention is to solve at least the above-mentioned problems and / or defects, and to provide at least the advantages described below.
[0004] To achieve these objectives and other advantages of the present invention, a purification and impurity control method for preparing high-purity metallic chromium is provided, comprising the following steps:
[0005] Step 1: Crush the chromium metal blocks produced by the electrothermal method and add them to the pretreatment chamber of the liquid nitrogen pulverizer. Pre-treat them at the set pre-cooling temperature, and then input them into the pulverizing chamber of the liquid nitrogen pulverizer. Pulverize them at the set pulverizing temperature until the particle size is ≤200 mesh chromium metal powder.
[0006] Step 2: Mix the chromium powder and additives evenly using a ball mill, then add the resulting mixture and binder to a high-shear mixer, mix evenly, and then press it into honeycomb briquette-like blocks using a molding device, and then dry it in a vacuum drying oven.
[0007] Step 3: Place the dried honeycomb-shaped blocks into a vacuum furnace for two-stage sintering: First, hold at a vacuum degree ≤100Pa and a temperature of 1000~1200℃ for 8~12h, then raise the temperature to 1300~1500℃, a vacuum degree ≤50Pa, and hold for 10~15h, then cool down with the furnace to obtain high-purity metallic chromium.
[0008] Preferably, in step one, the chromium metal block produced by the electrothermal method contains C ≤ 0.5 wt%, S ≤ 0.02 wt%, O ≤ 0.1 wt%, and N ≤ 0.01 wt%.
[0009] Preferably, in step one, the pre-cooling temperature of the liquid nitrogen pulverizer is -110 to -140°C, the pretreatment time is 10 to 20 minutes, the pulverizing temperature is -140 to -160°C, and the pulverizer speed is 2000 to 4000 r / min.
[0010] Preferably, in step two, the additives are chromium trioxide and tin powder; the mass ratio of chromium trioxide to C in the metallic chromium powder is 1.0 to 1.2:1, and the mass ratio of tin powder to S in the metallic chromium powder is 2 to 4:1.
[0011] Preferably, the chromium trioxide has a main content of ≥99.9% and a particle size of ≤200 mesh; the tin powder has a main content of ≥99.9% and a particle size of ≤200 mesh.
[0012] Preferably, in step two, the adhesive is water glass, epoxy resin, phenolic resin or furfuryl alcohol resin; the mass ratio of the mixture to the adhesive is 90-110:3.
[0013] Preferably, in step two, the total mass ratio of metallic chromium powder and additives to the mass of grinding balls in the ball mill is 1:3 to 5; the ball milling speed is 200 to 400 r / min; the ball milling time is 2 to 4 h; the high-shear mixer speed is 1000 to 3000 r / min; the mixing time is 20 to 40 min; the pressure parameters for molding are 10 to 40 MPa; and the drying temperature is 100 to 300 °C.
[0014] Preferably, in step two, the honeycomb-shaped block has a diameter of 15-30 cm and a height of 15-20 cm, and has evenly distributed circular air vents with a diameter of 8-12 mm.
[0015] Preferably, in step three, the high-purity metallic chromium obtained contains Cr ≥ 99.9 wt%, C ≤ 0.02 wt%, S ≤ 0.002 wt%, O ≤ 0.03 wt%, and N ≤ 0.002 wt%.
[0016] Preferably, step three further includes: during furnace cooling, hydrogen gas is introduced, the vacuum degree is controlled at 500-1000 Pa, and after the temperature drops to 200°C, inert gas is introduced to standard atmospheric pressure, and the furnace is removed to obtain high-purity metallic chromium.
[0017] Preferably, the inert gas is argon or helium.
[0018] The present invention has at least the following beneficial effects:
[0019] (1) Based on the characteristics of ordinary metallic chromium in the electrothermal process being brittle and easily crushed at low temperatures, this invention uses a liquid nitrogen pulverizer to grind and powder the chromium powder to obtain a uniform particle size. Then, a ball mill is used to grind and mix the powder, making the metallic chromium powder and additives more uniformly mixed, increasing the contact area of the mixture, which is more conducive to the reaction. Then, a high-shear mixer is used to mix the powder and the binder. The high shear effect can effectively improve the mixing efficiency and prevent the material from agglomerating.
[0020] (2) The present invention uses chromium trioxide and tin powder as additives and utilizes the high-temperature reduction reaction of the two under vacuum conditions to remove impurities, resulting in a product with extremely low impurity elements. The present invention mixes the mixture with the binder and presses it into a honeycomb-shaped block, which enables the gas generated in the reaction to be efficiently discharged and extracted under vacuum, thereby improving the removal efficiency of impurity elements such as C, O, N, and S.
[0021] (3) The present invention adopts two-stage sintering, which reduces the sublimation loss of metallic chromium under high temperature and high vacuum.
[0022] (4) When the furnace is cooled down, hydrogen gas is introduced to remove the residual oxygen and other gaseous elements in the reactants by utilizing the reducing properties of hydrogen, thereby further improving the purity of metallic chromium to 99.99 wt%.
[0023] (5) The high-purity metallic chromium prepared by this invention contains Cr ≥ 99.9 wt%, C ≤ 0.02 wt%, S ≤ 0.002 wt%, O ≤ 0.03 wt%, and N ≤ 0.002 wt%, which meets the stringent requirements of special equipment in aerospace, nuclear power and other fields for metallic chromium.
[0024] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Detailed Implementation
[0025] The present invention will be further described in detail below with reference to embodiments, so that those skilled in the art can implement it based on the description.
[0026] It should be understood that terms such as “having,” “comprising,” and “including” as used herein do not exclude the presence or addition of one or more other elements or combinations thereof.
[0027] Example 1
[0028] A method for purifying and controlling impurities in the preparation of high-purity metallic chromium includes the following steps:
[0029] Step 1: Crush the metallic chromium blocks produced by the electrothermal method and add them to the pretreatment chamber of the liquid nitrogen pulverizer. Pre-treat them at -130℃ for 15 minutes, and then input them into the pulverizing chamber of the liquid nitrogen pulverizer. Pulverize them at -150℃ with a pulverizer speed of 3000 r / min until they are pulverized into metallic chromium powder with a particle size of 200 mesh.
[0030] Step 2: Add 10 kg of metallic chromium powder to a ball mill, then add chromium trioxide (main content ≥ 99.9%, particle size 200 mesh) and tin powder (main content ≥ 99.9%, particle size 200 mesh). The total mass ratio of metallic chromium powder, chromium trioxide, and tin powder to the mass of the grinding balls is 1:4. The milling speed is 300 r / min, and the milling time is 3 hours to obtain a mixture. Add the mixture and water glass at a mass ratio of 100:3 to a high-shear mixer and mix at 2000 r / min. After 30 minutes, the mixture was pressed into honeycomb-shaped blocks using a molding device at a pressure of 25 MPa. The honeycomb-shaped blocks had a diameter of 25 cm and a height of 18 cm, with evenly distributed circular air vents of 10 mm in diameter. They were then dried in a vacuum drying oven at 200 °C. Analysis showed that the chromium powder contained 0.44 wt% C, 0.016 wt% S, 0.044 kg of chromium trioxide, and 0.0032 kg of tin powder.
[0031] Step 3: Place the dried honeycomb-shaped blocks into a vacuum furnace for two-stage sintering: First, maintain the temperature at 1000℃ and a vacuum of 100Pa for 8 hours, then raise the temperature to 1300℃, maintain the temperature at 50Pa and a vacuum of 10 hours, and then cool down with the furnace to obtain high-purity metallic chromium.
[0032] The elemental composition of the high-purity metallic chromium obtained in this embodiment is shown in Table 1.
[0033] Table 1
[0034] Content (wt%) 99.92 0.018 0.0015 0.027 0.002
[0035] Example 2
[0036] In this embodiment, the amount of chromium trioxide used is 0.0484 kg, the amount of tin powder used is 0.0048 kg, and the remaining steps are the same as in Example 1.
[0037] The elemental composition of the high-purity metallic chromium obtained in this embodiment is shown in Table 2.
[0038] Table 2
[0039] Content (wt%) 99.96 0.011 0.001 0.018 0.0012
[0040] Example 3
[0041] In this embodiment, the amount of chromium trioxide used is 0.0528 kg, the amount of tin powder used is 0.0064 kg, and the remaining steps are the same as in Example 1.
[0042] The elemental composition of the high-purity metallic chromium obtained in this embodiment is shown in Table 3.
[0043] Table 3
[0044] Content (wt%) 99.95 0.01 0.0012 0.023 0.0016
[0045] Example 4
[0046] The two-stage sintering in this embodiment is as follows: First, under a vacuum of 80 Pa and a temperature of 1100 °C, the temperature is held for 10 hours. Then, the temperature is raised to 1400 °C, the vacuum is 30 Pa, and the temperature is held for 12 hours. The temperature is then lowered with the furnace. The remaining steps are the same as in Embodiment 2.
[0047] The elemental composition of the high-purity metallic chromium obtained in this embodiment is shown in Table 4.
[0048] Table 4
[0049] Content (wt%) 99.97 0.0083 0.001 0.014 0.001
[0050] Example 5
[0051] The two-stage sintering in this embodiment is as follows: First, under a vacuum of 50 Pa and a temperature of 1200 °C, the temperature is held for 12 hours. Then, the temperature is raised to 1500 °C, the vacuum is 10 Pa, and the temperature is held for 15 hours. The temperature is then lowered with the furnace. The remaining steps are the same as in Embodiment 2.
[0052] The elemental composition of the high-purity metallic chromium obtained in this embodiment is shown in Table 5.
[0053] Table 5
[0054] Content (wt%) 99.96 0.01 0.0014 0.015 0.0011
[0055] Example 6
[0056] In this embodiment, water glass is replaced with phenolic resin, and the remaining steps are the same as in Example 4.
[0057] The elemental composition of the high-purity metallic chromium obtained in this embodiment is shown in Table 6.
[0058] Table 6
[0059] Content (wt%) 99.95 0.015 0.0017 0.025 0.0014
[0060] Example 7
[0061] In this embodiment, hydrogen gas is introduced during furnace cooling, the vacuum degree is controlled at 800 Pa, and after the temperature drops to 200°C, argon gas is introduced to standard atmospheric pressure. The furnace is then removed to obtain high-purity metallic chromium. The remaining steps are the same as in Example 4.
[0062] Analysis shows that the elemental composition of the high-purity metallic chromium obtained in this embodiment is shown in Table 7. It can be seen that, compared with Example 4, in this embodiment, hydrogen gas is introduced during furnace cooling. The reducing properties of hydrogen are used to remove residual oxygen and other gaseous elements in the reactants, further improving the purity of metallic chromium to 99.99 wt%.
[0063] Table 7
[0064] Content (wt%) 99.99 0.0022 0.0008 0.0052 0.0007
[0065] Comparative Example 1
[0066] A method for purifying and controlling impurities in metallic chromium includes the following steps:
[0067] Step 1: Crush the chromium metal blocks produced by the electrothermal method and grind them into chromium metal powder with a particle size of 200 mesh;
[0068] Step 2: Add 10 kg of metallic chromium powder to a ball mill, then add chromium trioxide (main content ≥ 99.9%, particle size 200 mesh) and tin powder (main content ≥ 99.9%, particle size 200 mesh). The total mass ratio of metallic chromium powder, chromium trioxide, and tin powder to the mass of the grinding balls is 1:4. The milling speed is 300 r / min, and the milling time is 3 hours to obtain a mixture. Add the mixture and water glass at a mass ratio of 100:3 to a high-shear mixer and mix at 2000 r / min. After 30 minutes, the mixture was pressed into honeycomb-shaped blocks using a molding device at a pressure of 25 MPa. The honeycomb-shaped blocks had a diameter of 25 cm and a height of 18 cm, with evenly distributed circular air vents of 10 mm in diameter. They were then dried in a vacuum drying oven at 200 °C. Analysis showed that the chromium powder contained 0.44 wt% C, 0.016 wt% S, 0.0484 kg of chromium trioxide, and 0.0048 kg of tin powder.
[0069] Step 3: Place the dried honeycomb-shaped blocks into a vacuum furnace for two-stage sintering: First, hold at a vacuum of 80 Pa and a temperature of 1100 °C for 10 hours, then raise the temperature to 1400 °C, maintain a vacuum of 30 Pa, hold for 12 hours, and then cool down with the furnace to obtain metallic chromium.
[0070] Analysis shows that the elemental composition of the metallic chromium obtained in this comparative example is shown in Table 8. It can be seen that, compared with Example 4, this comparative example did not use a liquid nitrogen pulverizer for grinding and powdering, resulting in uneven particle size distribution of metallic chromium powder and reduced purification and impurity control effect.
[0071] Table 8
[0072] Content (wt%) 99.71 0.13 0.0018 0.071 0.006
[0073] Comparative Example 2
[0074] A method for purifying and controlling impurities in metallic chromium includes the following steps:
[0075] Step 1: Crush the metallic chromium blocks produced by the electrothermal method and add them to the pretreatment chamber of the liquid nitrogen pulverizer. Pre-treat them at -130℃ for 15 minutes, and then input them into the pulverizing chamber of the liquid nitrogen pulverizer. Pulverize them at -150℃ with a pulverizer speed of 3000 r / min until they are pulverized into metallic chromium powder with a particle size of 200 mesh.
[0076] Step 2: Mix 10 kg of metallic chromium powder, chromium trioxide (main content ≥99.9%, particle size 200 mesh), and tin powder (main content ≥99.9%, particle size 200 mesh) with water glass at a mass ratio of 100:3 in a high-shear mixer. Mix at 2000 r / min for 30 min. Use a molding device to press it into honeycomb-shaped blocks at a pressure of 25 MPa. The honeycomb-shaped blocks have a diameter of 25 cm and a height of 18 cm, with evenly distributed circular air vents of 10 mm in diameter. Then dry them in a vacuum drying oven at 200℃. Analysis shows that the metallic chromium powder contains 0.44 wt% C and 0.016 wt% S, 0.0484 kg of chromium trioxide, and 0.0048 kg of tin powder.
[0077] Step 3: Place the dried honeycomb-shaped blocks into a vacuum furnace for two-stage sintering: First, hold at a vacuum of 80 Pa and a temperature of 1100 °C for 10 hours, then raise the temperature to 1400 °C, maintain a vacuum of 30 Pa, hold for 12 hours, and then cool down with the furnace to obtain metallic chromium.
[0078] Analysis shows that the elemental composition of the high-purity metallic chromium obtained in this comparative example is shown in Table 9. It can be seen that, compared with Example 4, this comparative example did not use a ball mill for grinding and mixing, and the metallic chromium powder and additives were not mixed evenly, which reduced the purification and impurity control effect.
[0079] Table 9
[0080] Content (wt%) 99.63 0.31 0.0042 0.037 0.005
[0081] Comparative Example 3
[0082] A method for purifying and controlling impurities in metallic chromium includes the following steps:
[0083] Step 1: Crush the metallic chromium blocks produced by the electrothermal method and add them to the pretreatment chamber of the liquid nitrogen pulverizer. Pre-treat them at -130℃ for 15 minutes, and then input them into the pulverizing chamber of the liquid nitrogen pulverizer. Pulverize them at -150℃ with a pulverizer speed of 3000 r / min until they are pulverized into metallic chromium powder with a particle size of 200 mesh.
[0084] Step 2: Add 10 kg of metallic chromium powder to a ball mill, then add chromium trioxide (main content ≥ 99.9%, particle size 200 mesh) and tin powder (main content ≥ 99.9%, particle size 200 mesh). The total mass ratio of metallic chromium powder, chromium trioxide, and tin powder to the mass of the grinding balls is 1:4. The rotation speed is 300 r / min, and the ball milling time is 3 hours to obtain a mixture. Add the mixture and water glass to a mixer at a mass ratio of 100:3, and mechanically mix at 1000 r / min. After stirring for 3 hours, the mixture was pressed into honeycomb-shaped blocks using a molding device at a pressure of 25 MPa. The honeycomb-shaped blocks had a diameter of 25 cm and a height of 18 cm, with evenly distributed circular air vents of 10 mm in diameter. They were then dried in a vacuum drying oven at 200 °C. Analysis showed that the chromium powder contained 0.44 wt% C, 0.016 wt% S, 0.0484 kg of chromium trioxide, and 0.0048 kg of tin powder.
[0085] Step 3: Place the dried honeycomb-shaped blocks into a vacuum furnace for two-stage sintering: First, hold at a vacuum of 80 Pa and a temperature of 1100 °C for 10 hours, then raise the temperature to 1400 °C, maintain a vacuum of 30 Pa, hold for 12 hours, and then cool down with the furnace to obtain metallic chromium.
[0086] Analysis shows that the elemental composition of the high-purity metallic chromium obtained in this comparative example is shown in Table 10. It can be seen that, compared with Example 4, this comparative example did not use a high-shear mixer to mix the powder and binder, resulting in low stirring efficiency and uneven mixing, which reduced the purification and impurity control effect.
[0087] Table 10
[0088] Content (wt%) 99.61 0.28 0.002 0.04 0.008
[0089] Comparative Example 4
[0090] A method for purifying and controlling impurities in metallic chromium includes the following steps:
[0091] Step 1: Crush the metallic chromium blocks produced by the electrothermal method and add them to the pretreatment chamber of the liquid nitrogen pulverizer. Pre-treat them at -130℃ for 15 minutes, and then input them into the pulverizing chamber of the liquid nitrogen pulverizer. Pulverize them at -150℃ with a pulverizer speed of 3000 r / min until they are pulverized into metallic chromium powder with a particle size of 200 mesh.
[0092] Step 2: Add 10 kg of metallic chromium powder to a ball mill, then add chromium trioxide (main content ≥99.9%, particle size 200 mesh) and tin powder (main content ≥99.9%, particle size 200 mesh). The total mass ratio of metallic chromium powder, chromium trioxide, and tin powder to the mass of the grinding balls is 1:4. The rotation speed is 300 r / min, and the ball milling time is 3 hours to obtain a mixture. Add the mixture and water glass at a mass ratio of 100:3 to a high-shear mixer and mix at 2000 r / min for 30 minutes. Use a molding device to press it into a solid cylinder with a diameter of 25 cm and a height of 18 cm, with a pressure parameter of 25 MPa. Then dry it in a vacuum drying oven at 200℃. The analysis shows that the C content of the metallic chromium powder is 0.44 wt%, the S content is 0.016 wt%, the amount of chromium trioxide is 0.0484 kg, and the amount of tin powder is 0.0048 kg.
[0093] Step 3: Place the dried honeycomb-shaped blocks into a vacuum furnace for two-stage sintering: First, hold at a vacuum of 80 Pa and a temperature of 1100 °C for 10 hours, then raise the temperature to 1400 °C, maintain a vacuum of 30 Pa, hold for 12 hours, and then cool down with the furnace to obtain metallic chromium.
[0094] Analysis shows that the elemental composition of the high-purity metallic chromium obtained in this comparative example is shown in Table 11. It can be seen that, compared with Example 4, this comparative example, after mixing the mixture with the binder, is pressed into a solid cylinder without any air pores. As a result, the gas generated during the reaction cannot be efficiently discharged, which reduces the purification and impurity control effect.
[0095] Table 11
[0096] Content (wt%) 99.75 0.16 0.011 0.029 0.005
[0097] Comparative Example 5
[0098] A method for purifying and controlling impurities in metallic chromium includes the following steps:
[0099] Step 1: Crush the metallic chromium blocks produced by the electrothermal method and add them to the pretreatment chamber of the liquid nitrogen pulverizer. Pre-treat them at -130℃ for 15 minutes, and then input them into the pulverizing chamber of the liquid nitrogen pulverizer. Pulverize them at -150℃ with a pulverizer speed of 3000 r / min until they are pulverized into metallic chromium powder with a particle size of 200 mesh.
[0100] Step 2: Add 10 kg of metallic chromium powder to a ball mill, then add chromium trioxide (main content ≥ 99.9%, particle size 200 mesh) and tin powder (main content ≥ 99.9%, particle size 200 mesh). The total mass ratio of metallic chromium powder, chromium trioxide, and tin powder to the mass of the grinding balls is 1:4. The milling speed is 300 r / min, and the milling time is 3 hours to obtain a mixture. Add the mixture and water glass at a mass ratio of 100:3 to a high-shear mixer and mix at 2000 r / min. After 30 minutes, the mixture was pressed into honeycomb-shaped blocks using a molding device at a pressure of 25 MPa. The honeycomb-shaped blocks had a diameter of 25 cm and a height of 18 cm, with evenly distributed circular air vents of 10 mm in diameter. They were then dried in a vacuum drying oven at 200 °C. Analysis showed that the chromium powder contained 0.44 wt% C, 0.016 wt% S, 0.0484 kg of chromium trioxide, and 0.0048 kg of tin powder.
[0101] Step 3: Place the dried honeycomb-shaped blocks into a vacuum furnace for sintering: at a vacuum of 30 Pa and a temperature of 1400 °C, hold for 22 hours, then cool down with the furnace to obtain metallic chromium.
[0102] Analysis shows that the elemental composition of the high-purity metallic chromium obtained in this comparative example is shown in Table 12. It can be seen that, compared with Example 4, this comparative example undergoes a single sintering process, which removes impurities but also results in the sublimation loss of metallic chromium, leading to poor final purification and impurity control.
[0103] Table 12
[0104] Content (wt%) 99.77 0.15 0.009 0.047 0.006
[0105] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and embodiments shown and described herein.
Claims
1. A method for purifying and controlling impurities in the preparation of high-purity metallic chromium, characterized in that, Includes the following steps: Step 1: Crush the metallic chromium blocks produced by the electrothermal aluminothermic process and add them to the pretreatment chamber of a liquid nitrogen pulverizer. Pre-treat them at a set pre-cooling temperature, then feed them into the pulverizing chamber of the liquid nitrogen pulverizer and pulverize them at a set pulverizing temperature until they are pulverized to metallic chromium powder with a particle size ≤200 mesh. The pre-cooling temperature of the liquid nitrogen pulverizer is -110~-140℃, the pretreatment time is 10~20min, the pulverizing temperature is -140~-160℃, and the pulverizer speed is 2000~4000r / min. Step 2: Mix metallic chromium powder and additives evenly using a ball mill. Then, add the resulting mixture and binder to a high-shear mixer and mix evenly. After mixing, press the mixture into honeycomb-shaped blocks using a molding device, and then dry it in a vacuum drying oven. The additives are chromium trioxide and tin powder. The mass ratio of chromium trioxide to carbon in the metallic chromium powder is 1.1~1.2:1, and the mass ratio of tin powder to sulfur in the metallic chromium powder is 3~4:
1. The honeycomb-shaped blocks have a diameter of 15~30cm and a height of 15~20cm, and are uniformly distributed with circular air vents with a diameter of 8~12mm. Step 3: Place the dried honeycomb-shaped blocks into a vacuum furnace for two-stage sintering: First, maintain a vacuum of ≤100Pa and a temperature of 1000~1200℃ for 8~12 hours. Then, raise the temperature to 1300~1500℃, maintain a vacuum of ≤50Pa, and maintain the temperature for 10~15 hours. Cool down the furnace while introducing hydrogen gas, control the vacuum at 500~1000Pa, and after the temperature drops to 200℃, introduce inert gas to standard atmospheric pressure. Remove from the furnace to obtain high-purity metallic chromium.
2. The purification and impurity control method for preparing high-purity metallic chromium as described in claim 1, characterized in that, In step one, the metallic chromium block produced by the electrothermal method contains C≤0.5wt%, S≤0.02wt%, O≤0.1wt%, and N≤0.01wt%.
3. The purification and impurity control method for preparing high-purity metallic chromium as described in claim 1, characterized in that, The chromium trioxide has a main content of ≥99.9% and a particle size of ≤200 mesh; the tin powder has a main content of ≥99.9% and a particle size of ≤200 mesh.
4. The purification and impurity control method for preparing high-purity metallic chromium as described in claim 1, characterized in that, In step two, the adhesive is water glass, epoxy resin, phenolic resin or furfuryl alcohol resin; the mass ratio of the mixture to the adhesive is 90~110:
3.
5. The purification and impurity control method for preparing high-purity metallic chromium as described in claim 1, characterized in that, In step two, the total mass ratio of metallic chromium powder and additives to the mass of grinding balls in the ball mill is 1:3~5, the ball milling speed is 200~400 r / min, and the ball milling time is 2~4 h; the high shear mixer speed is 1000~3000 r / min, and the mixing time is 20~40 min; the pressure parameter for molding is 10~40 MPa; and the drying temperature is 100~300℃.
6. The purification and impurity control method for preparing high-purity metallic chromium as described in claim 1, characterized in that, In step three, the obtained high-purity metallic chromium contains Cr ≥ 99.9 wt%, C ≤ 0.02 wt%, S ≤ 0.002 wt%, O ≤ 0.03 wt%, and N ≤ 0.002 wt%.
Citation Information
Patent Citations
Production method for preparing high pure chromium metal special for high temperature alloy and target material through composite degassing agent
CN107904410A
Production method of high-purity chromium
CN111378832A
Purification process for chromium
CN1311723A